Shear stress and oxygen availability drive differential changes in opossum kidney proximal tubule cell metabolism and endocytosis. (9th May 2019) - Ren, Qidong; Gliozzi, Megan L.; Rittenhouse, Natalie L.; Edmunds, Lia R.; Rbaibi, Youssef; Locker, Joseph D.; Poholek, Amanda C.; Jurczak, Michael J.; Baty, Catherine J.; Weisz, Ora A.
Abstract: Kidney proximal tubule (PT) cells have high‐metabolic demands to drive the extraordinary ion and solute transport, water reabsorption, and endocytic uptake that occur in this nephron segment. Increases in renal blood flow alter glomerular filtration rate and lead to rapid mechanosensitive adaptations in PT transport, impacting metabolic demand. Although the PT reabsorbs essentially all of the filtered glucose, PT cells rely primarily on oxidative metabolism rather than glycolysis to meet their energy demands. We lack an understanding of how PT functions are impacted by changes in O2 availability via cortical capillaries and mechanosensitive signaling in response to alterations in luminal flow. Previously, we found that opossum kidney (OK) cells recapitulate key features of PT cells in vivo, including enhanced endocytic uptake and ion transport, when exposed to mechanical stimulation by culture on an orbital shaker. We hypothesized that increased oxygenation resulting from orbital shaking also contributes to this more physiologic phenotype. RNA seq of OK cells maintained under static conditions or exposed to orbital shaking for up to 96 hours showed significant time‐ and culture‐dependent changes in gene expression. Transcriptional and metabolomics data were consistent with a decrease in glycolytic flux and with an increased utilization of aerobic metabolic pathways in cells exposed to orbital shaking. Moreover, we found spatial differences in the pattern of mitogenesis vs development of ion transport and endocytic capacities in our culture system that highlight the complexity of O2 ‐dependent and mechanosensitive crosstalk to regulate PT cell function. Abstract : The proximal tubule (PT) relies primarily on oxidative metabolism rather than glycolysis to meet the high‐energy demands needed to drive ion transport and endocytic reclamation of filtered proteins. Many of the available model cell lines fail to replicate the key features of this nephron segment. We found that culturing PT cells under continuous shear stress enhances cell differentiation and drives a metabolic shift toward oxidative metabolism. Moreover, oxygen availability and shear stress differentially regulate PT responses in this culture model.